Interparental conflict and adolescents’ suicidal ideation: life satisfaction as a mediator and teacher support as a moderator - Xu, Lu; She, Zhuang; Xu, Baohua (Frontiers in Public Health, 2025)
BackgroundSuicidal ideation is the most significant risk factor for suicide, and suicide is the third leading cause of death among people aged 15 to 19 years. Interparental conflict has been shown to be associated with adolescents’ suicidal ideation, but the reasons for this association remain underexplored. We investigated whether adolescents’ life satisfaction accounts for this relationship, and whether perceived teacher support moderates the mediation process.MethodsA total of 649 Chinese adolescents (52% girls; mean age = 15.59 years, SD = 0.70) completed anonymous questionnaires in their classroom to assess interparental conflict, life satisfaction, teacher support, and suicidal ideation. The data were analyzed using SPSS 26.0 software.ResultsThe mediation analysis showed that a significant indirect relationship between interparental conflict and suicidal ideation, mediated by life satisfaction (β = 0.02, 95% CI [0.01, 0.04]). The moderation analysis revealed that teacher support moderated the relationship between life satisfaction and suicidal ideation (β = −0.03, p < 0.01). The relationship between life satisfaction and suicidal ideation was significant for adolescents who perceived high teacher support (β = −0.08, 95% CI [−0.12, −0.04]) but not for those who perceived low teacher support (β = −0.01, 95% CI [−0.05, 0.03]).DiscussionThe study suggest that life satisfaction and teacher support are important protective factors for adolescent suicidal ideation. Life satisfaction was associated with less suicidal ideation for adolescents with high rather than low teacher support. These findings point to the importance of considering school, family, and individual factors concurrently when developing programs to prevent and reduce adolescents’ suicidal ideation.